Modeling and Global Sensitivity Analysis of a Solar Powered Air Cooling System Using Liquid Desiccant - Rakotondramiarana, Hery Tiana; Andrianomena, Sambatra Hagatiana; Andriamamonjy, Ando Ludovic; Rakotomalala, Minoson Sendrahasina (Journal of Technology Innovations in Renewable Energy, 2013)
Solar energy technology is an option for energy saving in building air conditioning. A theoretical investigation of an open cycle solar air cooling system using aqueous Lithium Chloride solution as liquid desiccant is presented in this paper. The purpose of this work is to analyze the influences of both internal loads and external forcing, on the studied system by developing a computational code related to its mathematical model. The simulation results justify the choice of the system design. Indeed, it was highlighted that the higher is the outdoor temperature; the better is the coefficient of performance (COP) of the system. Furthermore, a global sensitivity analysis of the system model, achieved using Fourier Amplitude Sensitivity Test method, allowed us to identify the most influential factors that were ranked in a decreasing order of their influence degree on the system COP. Hence, key factors to be controlled for improving the system overall performance are specified.